Association of carotid wall shear stress measured by vector flow mapping technique with ba-PWV: a pilot study - Cheng, Yi; Chen, Jie; Zhao, Qing; Zhang, Jinghan; Gao, Junyi (Frontiers in Cardiovascular Medicine, 2023)
Objective: Arterial stiffness is an important tissue biomarker of the progression of atherosclerotic diseases. Brachial-ankle pulse wave velocity (ba-PWV) is a gold standard of arterial stiffness measurement widely used in Asia. Changes in vascular wall shear stress (WSS) lead to artery wall remodeling which could give rise to increase in arterial stiffness. The study aimed to explore the association between ba-PWV and common carotid artery (CCA) WSS measured by a newly invented vascular vector flow mapping (VFM) technique.We included 94 subjects free of apparent cardiovascular disease (CVD) and divided them into subclinical atherosclerosis (SA) group (N=47) and non subclinical atherosclerosis (NSA) group (N=47). CCA WSS was measured using the VFM technique. Bivariate correlations between CCA WSS and other factors were assessed with Pearson's, Spearman's or Kendall's coefficient of correlation, as appropriate. Partial correlation analysis was conducted to examine the influence of age and sex. Multiple linear stepwise regression was used for analysis of independent determinants of CCA WSS. Receiver operating characteristic (ROC) analysis was performed to find the association between CCA WSS and 10-year CVD risk.The overall subjects had a mean age of 47.9±11.2 years and males accounted for 52.1%.Average systolic CCA WSS was significantly correlated with ba-PWV (r=-0.618, p<0.001) in SA group. Multiple linear stepwise regression analysis confirmed that ba-PWV was an independent determinant of average systolic CCA WSS (β=-0.361, p=0.003). Area under the curve (AUC) of average systolic CCA WSS for 10-year CVD risk ≥ 10% was 0.848 (p<0.001) in SA group.Conclusions: Average systolic CCA WSS was significantly correlated with ba-PWV and was associated with 10-year CVD risk ≥ 10% in SA group. Therefore, CCA WSS measured by the VFM technique could be used for monitoring and screening of subjects with potential CVD risks.